2016
DOI: 10.1002/2016gc006256
|View full text |Cite
|
Sign up to set email alerts
|

Choosing optimal exposure times for XRF core‐scanning: Suggestions based on the analysis of geological reference materials

Abstract: X‐ray fluorescence (XRF) core‐scanning is a fast and nondestructive technique to assess elemental variations of unprocessed sediments. However, although the exposure time of XRF‐scanning directly affects the scanning counts and total measurement time, only a few studies have considered the influence of exposure time during the scan. How to select an optimal exposure time to achieve reliable results and reduce the total measurement time is an important issue. To address this question, six geological reference m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…With 100 seconds exposure time, the correlation coefficients between scanning intensities and reference concentrations of laboratory-prepared reference resins are all higher than 0.97 for pollution related elements such as Cr, Mn, Ni, Cu, Zn, and Pb. Moreover, as suggested by Huang et al (2016) from the experience of sediment reference standards, the strong linear relationship between scanning intensities and reference concentrations of resins remains similar even with exposure time as brief as 1 second. Thus, this method provides a fast and inexpensive method to quantitatively assess multiple element concentrations in the resins, and can be used as an environmental monitoring tool for large geographic areas in order to understand the variations of environmental contaminants across a landscape.…”
Section: Ion Exchange Resin Samplesmentioning
confidence: 56%
“…With 100 seconds exposure time, the correlation coefficients between scanning intensities and reference concentrations of laboratory-prepared reference resins are all higher than 0.97 for pollution related elements such as Cr, Mn, Ni, Cu, Zn, and Pb. Moreover, as suggested by Huang et al (2016) from the experience of sediment reference standards, the strong linear relationship between scanning intensities and reference concentrations of resins remains similar even with exposure time as brief as 1 second. Thus, this method provides a fast and inexpensive method to quantitatively assess multiple element concentrations in the resins, and can be used as an environmental monitoring tool for large geographic areas in order to understand the variations of environmental contaminants across a landscape.…”
Section: Ion Exchange Resin Samplesmentioning
confidence: 56%
“…The 10 th percentile of the distribution, which avoids outliers at the tail of the SNR distribution, could be used to determine whether particular values of tube voltage, current and exposure time are likely to deliver measurements above the LOQ for the majority of the element profile. Although Huang et al (2016) concluded that increasing Itrax XRF exposure time gives insignificant improvements in accuracy, Figure 4 demonstrates that for elements such as Rb and Zr increasing exposure time can substantially increase the proportion of measurements with SNRs greater than the LOQ.…”
Section: The Factors Inmentioning
confidence: 98%
“…The scanner was fitted with a Mo-tube and a magnetic susceptibility meter, with XRF scans performed on each core at 30 kV and 55 mA using 10 s exposure time and sampled at 500 μm step size. In comparison, Itrax analysis of the Little Pigeon Bay cores were carried out using similar settings at the University of Auckland [8], with a negligible difference of 4 s exposure time between the two datasets [20].…”
Section: Itrax Data and Analysismentioning
confidence: 99%